Two new species of Hemiphyllodactylus (Squamata: Gekkonidae) from Hoa Binh Province, Vietnam - Nguyen, Truong Quang; Do, Quyen Hanh; Ngo, Hanh Thi; van Pham, Anh; Pham, Cuong The; Le, Minh Duc; Ziegler, Thomas (Zootaxa, 2020)
We describe two new species of the genus Hemiphyllodactylus on the basis of a new collection of geckos from limestone karst forest of Hoa Binh Province, northwestern Vietnam. Hemiphyllodactylus bonkowskii sp. nov. from Hang Kia—Pa Co Nature Reserve and Hemiphyllodactylus ngocsonensis sp. nov. from Ngoc Son—Ngo Luong Nature Reserve can be distinguished from each other and from their congeners by genetic distinction and morphological differences in circumnasal scales, chin scales, precloacal and femoral pores, cloacal spurs, dorsal scales, ventral scales, digital lamellae formula, and color pattern. In phylogenetic analyses, both new species are nested in a clade that includes H. dushanensis, H. flaviventris, H. hongkongensis, H. huishuiensis, H. kiziriani, H. serpispecus, and H. zugi. In terms of pairwise genetic distance, the two new species are at least 7.5%–8.5% divergent from other described species based on a fragment of the ND2 gene.